2014
DOI: 10.1002/arch.21174
|View full text |Cite
|
Sign up to set email alerts
|

IDENTIFICATION AND FUNCTIONAL CHARACTERIZATION OF A PEPTIDOGLYCAN RECOGNITION PROTEIN FROM THE COTTON BOLLWORM, Helicoverpa armigera

Abstract: Peptidoglycan recognition proteins (PGRPs) specifically bind to peptidoglycans, and play crucial roles as pattern recognition receptors (PRRs) in mediating innate immune responses. In this study, we identified and characterized a PGRP (HaPGRP-D) from the cotton bollworm, Helicoverpa armigera. Sequence analysis indicated that HaPGRP-D is an amidase-type PGRP. Expression of HaPGRP-D was upregulated in the hemocytes of H. armigera larvae after injecting Gram-negative Escherichia coli, Gram-positive Staphylococcus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 52 publications
3
14
0
Order By: Relevance
“…We have identified nine putative PGRP transcripts in H. armigera transcriptome and have named them as HaPGRP-SA1 , − SA2 , − SB1 , − SB2 , − SD , − LA , − LB , − LC , − LD , in accordance with PGRP nomenclature from other insects (Figure 3 , in Additional file 6 : Table S5) [ 17 ]. The mRNA abundances of H. armigera PGRP-SA1, −SB1, and -SD increased in response to the bacterial infection, and their roles in bacteria agglutination and growth inhibition have been characterized as well [ 30 ]. Multiple sequence alignment suggested that PGRP-SB1 , − SB2 , − SD contains all the five active site residues (H, Y, H, T, C) essential for amidase activity, indicating that they can not only bind but also degrade peptidoglycan (in Additional file 1 : Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…We have identified nine putative PGRP transcripts in H. armigera transcriptome and have named them as HaPGRP-SA1 , − SA2 , − SB1 , − SB2 , − SD , − LA , − LB , − LC , − LD , in accordance with PGRP nomenclature from other insects (Figure 3 , in Additional file 6 : Table S5) [ 17 ]. The mRNA abundances of H. armigera PGRP-SA1, −SB1, and -SD increased in response to the bacterial infection, and their roles in bacteria agglutination and growth inhibition have been characterized as well [ 30 ]. Multiple sequence alignment suggested that PGRP-SB1 , − SB2 , − SD contains all the five active site residues (H, Y, H, T, C) essential for amidase activity, indicating that they can not only bind but also degrade peptidoglycan (in Additional file 1 : Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescein isothiocyanate (FITC) labeling of bacteria ( E. coli and S. aureus , 1 × 10 8 cells/ml) was performed according to the method reported by Li, Li, Song, et al. (). Then, FITC‐labeled bacterial suspension (10 μl) was combined with MdCTL1 or MdCTL2 (600 μg/ml, 20 μl) in the presence or absence of 10 mM CaCl 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Gram-negative bacteria E. coli and Gram-positive bacteria Staphylococcus aureus were used to measure the agglutinating activity of MdCTL1 and MdCTL2 using the method described by Wang et al (2012). Fluorescein isothiocyanate (FITC) labeling of bacteria (E. coli and S. aureus, 1 × 10 8 cells/ml) was performed according to the method reported by Li, Li, Song, et al (2014). Then, FITC-labeled bacterial suspension (10 l) was combined with MdCTL1 or MdCTL2…”
Section: Agglutination Assaymentioning
confidence: 99%
“…FITC labeling of bacteria was performed using the method described by Li et al (2014). In brief, heat-killed E. coli (10 9 cells/ml) were incubated in carbonate buffer (0.1 M Na2CO3, 0.1 M NaHCO3, pH 9.6) containing FITC (0.5 mg/ml) for 1 h in the dark.…”
Section: Phagocytosis Assaymentioning
confidence: 99%